Bridging the Gap: The Role of Apprenticeship Training Programs - Ramasamy Ravichandran (Journal of Vocational Education Studies, 2023)
This paper summarizes a study on the prospects and challenges of apprenticeship training programs for vocational students from schools in India. The study explores the current state of vocational education in India and the potential benefits of apprenticeship programs for students. It also discusses the challenges faced by the implementation of such programs, including the lack of coordination between educational institutions and industry, inadequate infrastructure, and inadequate regulatory framework. The study concludes that apprenticeship training programs have the potential to address the skills gap in India's workforce and improve the employability of vocational students, but significant efforts are needed to overcome the existing challenges and create a more supportive ecosystem for apprenticeship training programs in India.